(untitled) (Nepalese Journal of Management Research, 2024)
This study studied the perception of Balkumari College (BKC) students’ towards Finance professors (FP) also examining the teaching qualities of FP. The aim of this study was to identify the students’ perception towards FP, level of teaching quality and behavior of FP and tried to find out that how the FP’s communication skills, topics presentation, and guidance towards students was. The population of the study compared all students of BKC. The study sample consisted 376 students selected through the cluster and simple random sampling techniques from the Campus domain mail. The cross-sectional survey design was used and 26.16 % of data were collected from 24 self-made Five Likert scale (very poor to excellent) by questionnaires through a Google form. Data were analyzed by descriptive statistics using SPSS 20. The total number of male respondents were 72.20%, 70.20% were first-year and 57.6% were BKC students. The descriptive statistic showed the class management was more consistent than other teaching qualities and that FP was friendly, never rude and biased but proud. We concluded that professors should be well communicating, presenting the subject matter confidently, motivating towards research activities, and behave friendly and peaceful.